Lipid profiling of coral symbiosomes in response to copper-induced carbon limitation: A metabolic effect of algal symbionts on the host immune status. (April 2022) - Tang, Chuan-Ho; Shi, Shu-Han; Li, Hsing-Hui; Lin, Ching-Yu; Wang, Wei-Hsien
Abstract: Copper micropollutants are known to constrain coral's assimilation of carbonate, affecting the carbon available to algal symbionts and thus inducing a light stress. However, little is known regarding the physiological relevance of lipid metabolism in coral symbiotic algae in a carbon-limited state. Membrane lipids exhibit multiple physicochemical properties that are collectively responsible for the dynamic structure of cells depending on the physiological demands of the circumstances. To gain insight into lipid metabolism's importance in this regard, glycerophosphocholine (GPC) profiling of symbiosomes in coral ( Seriatopora caliendrum ) exposed to environmentally relevant copper levels (2.2–7.5 μg/L) for 4 days was performed in this study. Notably, reducing the number of 22:6-processing GPCs and increasing that of lyso-GPCs likely addressed the demands of metabolizing excess light energy, such as affecting the membrane dynamics to promote mitochondrial uncoupling. The decrease in 22:6-processing GPCs additionally protected cellular membranes from elevated oxidative stress, reducing their susceptibility to peroxidation and offsetting oxidized lipid-induced effects on membrane dynamics. The change in plasmanylcholines specifically localized within the symbiosome membrane also met the membrane requirements for responding to oxidative stress conditions. Moreover, increasing the 20:4-possessing plasmanylcholines and lysoplasmanylcholines and reducing the 22:6-possessing plasmanylcholines likely resulted in an imbalance of the immune reaction, influencing the coral–algae symbiosis given the role of such plasmanylcholines in cell signaling. In summary, carbon limitations induced by copper enrichment lead to a shift in the membrane lipid profile of coral symbiosomes, accommodating themselves to light stress conditions while compromising the symbiosis's stability. Graphical abstract: Image 1 Highlights: Copper makes algal symbiotes of coral a carbon limitation. Algae metabolizing excess energy involves a decrease of 22:6-possessing lipids. Symbiosome membrane raising 20:4-possessing lipids affects the symbiosis. Lipid changes also accommodate cellular membrane to oxidative stress. Modeling lipid variations be a tool of biomonitoring.